Excess Capacitance Due to Minority Carrier Injection in CrSi2/p-Type Crystalline Si Isotype Junction - Ozdemir, Orhan; Yilmazer, U. Deneb; Tatar, Beyhan; Urgen, Mustafa; Kutlu, Kubilay (IOP PUBLISHING LTD, 2010)
Excess current and capacitance phenonema were observed for the first time on a CrSi2/p-type crystalline silicon junction produced by cathodic arc physical vapor deposition. The heterojunction was investigated by current-voltage-temperature (I-V-T) and capacitance (conductance)-voltage/temperature (C, G-V/T) measurements for the purpose of studying transport and storage features. Excess current, manifested as a crossover at a large forward bias, was observed in I-V-T curves since minority carriers injected into the quasi-neutral region of p-c-Si were neutralized by majority carriers supplied from the p-c-Si semiconductor side. This phenomenon, known as conductivity modulation, appeared distinctly as a hump in C-V/T curves (storage property); a sharp rise in capacitance towards a maximum value as forward bias increased and the subsequent fall after a specific value. For reverse and low forward bias regions, where minority carrier injection was negligible, geometrical junction capacitance and a shoulder in C-V/T curves were observed. In the voltage range where the peak was observed in C-V/T measurements, trap-assisted tunneling recombination generation and space-charge-limited current (SCLC) mechanisms were determined in the CrSi2/p-c-Si isotype junction. Traps introduced during tunneling were identified as bulk point defects due to the chromium-boron (Cr-B) complex for the CrSi2/p-c-Si junction on the Si side by I-V-T and C(G)-T analyses. This finding seemed to be in agreement with a recent DLTS [Deep Level Transient Spectroscopy] measurement in terms of both energy depth (0.26 eV) and bulk nature. Finally, the shoulder in C-V/T curves indicated Cr-B point defects in the measurement. (C) 2010 The Japan Society of Applied Physics
Keywords: Physics